Pengaruh Good Governance dan F?nanc?al Performance terhadap K?nerja Perguruan T?ngg? pada Akadem? Keb?danan Salsab?la Serang Tahun 2017 - Andri Harpan (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Kesehatan Salsabila Serang, 2019)
In its development, the Salsabila Serang Midwifery Academy has decreased interest from the community, thus demanding higher education governance that leads to good university governance in accordance with the mandate of the ministry, the financial performance of non-profit entities and performance measurement systems based on financial and non-financial refers to education standards high. The research method used in this study is descriptive and verification. The data used are primary data and secondary data. Data collection was carried out through documentation and questionnaires or questionnaires on 30 respondents. Sampling using using saturated sampling (census). To measure the magnitude of the influence of the three variables used Spearman rank coefficient correlation analysis and determination coefficient and hypothesis testing. The results of the study and discussion and conclusions are as follows: (1) With the calculation of the coefficient of determination, the variable good university governance (X1) gives an effect of 22.47% on the variable of college performance (Y) hypothesis testing shows tcount of 3.683> t table of 2.051 . (2) With the calculation of the coefficient of determination, the variable financial performance (X2), gives an effect of 99.80% on the variable of college performance (Y) Hypothesis testing shows tcount of 37.768> t table of 2.051. (3) With the calculation of the coefficient of determination, the variable good university governance (X1), the variable financial performance (X2), gives an effect of 99.60% on the variable of college performance, the remaining 0.40% is influenced by other factors not examined by author. Hypothesis test shows 506,983> ftabel of 3,354 means that Good University Governance (X1) and Financial Performance (X2) have an influence on College Performance (Y).